Development of gas sensor array based on phthalocyanine functionalized bilayer TiO2:ZnO thin film towards l iver disease detection - Jareena Begam, J; Hariharan, M; Karthik Raj, V; Gnanavel, S; Sarathbavan, M; Yuvaraj, S (International Journal of Engineering and Technology, 2018)
This paper has been withdrawn